Design and development of energy efficient continuous cooking system. (January 2016) - Shinde, Yogesh H.; Gudekar, Ajitkumar S.; Chavan, Prakash V.; Pandit, Aniruddha B.; Joshi, Jyeshtharaj B.
Highlights: Continuous cooking system is developed. RTD of solid and liquid phases studied. Solid phase behaves in plug flow manner. Liquid phase behaves in backmixed manner. More efficient than convention cooking devices. Abstract: For large scale cooking, it is desirable to implement continuous cooking. In addition to the usual advantages of continuous cooking (size of cooker, uniform cooked quality, possibility of process control), there is a possibility of increasing the thermal efficiency by preheating water against the hot cooked food leaving the cooker. In the present work, solid and liquid phase residence time distribution (RTD) have been measured in 120 mm diameter and 1.6 m long continuous cooker. Three levels of screw speed (1, 3 and 5 rpm), two levels of solid flow rate (12and 24 kg/h) and three levels of liquid flow rate (15, 25 and 35 lph) were selected. The solid phase was always found to move in a plug flow manner as the minimum Peclet number was found to be 81.5. This information was found to be useful for deciding the capacity of the continuous cooker. Thus, the time required for batch cooking was found to be equal to the minimum residence time in a continuous cooker at equivalent operating condition of temperature.